No Way Out: Crime, Punishment and the Capitalization of Power - Shimshon Bichler; Jonathan Nitzan (Crime, Law and Social Change, 2014)
The United States is often hailed as the world's largest 'free market'. But this 'free market' is also the world's largest penal colony. It holds over seven million adults – roughly five per cent of the labour force – in jail, in prison, on parole and on probation. Is this an anomaly, or does the 'free market' require massive state punishment? Why did the correctional population start to rise in the 1980s, together with the onset of neoliberalism? How is this increase related to the upward redistribution of income and the capitalization of power? Can soaring incarceration sustain the unprecedented power of dominant capital, or is there a reversal in the offing? The paper examines these questions by juxtaposing the `Rusche thesis' with the notion of capitalism as a mode of power. The empirical analysis suggests that the Rusche thesis holds under the normal circumstances of `business as usual', but breaks down during periods of systemic crisis. During the systemic crises of the 1930s and the 2000s, unemployment increased sharply, but crime and the severity of punishment, instead of rising, dropped perceptibly.
Keywords: 330; capital as power; crime; Georg Rusche; punishment; systemic crisis; unemployment; United States